Smokers with MS have greater decrements in quality of life and disability than non-smokers. (November 2017) - Briggs, Farren BS; Gunzler, Douglas D; Ontaneda, Daniel; Marrie, Ruth Ann
Background: Tobacco smoke plays a pathogenic role in multiple sclerosis (MS) and may accelerate disease progression, yet, some people with MS continue to smoke after disease onset. The average smoker reports diminished health-related quality of life (HRQOL) across many populations. Objectives: To describe the relationships between smoking status and HRQOL, disease activity, and global disability in a US population with MS. Methods: We compared smokers to non-smokers in 950 responders to the Spring 2014 update survey completed by North American Research Committee on Multiple Sclerosis (NARCOMS) registry participants. HRQOL was assessed using Short Form-12 version 2 (SF-12v2), disease activity was investigated using eight Performance Scales (PS) and three Functionality Scales (FS). Global disability was evaluated using Patient Determined Disease Steps (PDDS) and an item response theory (IRT) summed score based on the PS and FS. Results: Smokers had lower HRQOL ( p < 0.0001), reported more disease activity ( p < 0.05) and greater deficits in all PS and FS ( p = 6 × 10 −7 to 0.05), except mobility. Smokers and non-smokers did not differ by PDDS but had substantially greater IRT global disability ( p = 2 × 10 −7 ). Conclusion: Active smoking is meaningfully associated with deficits across multiple domains in people with MS and adds to the growing literature of the need for MS-tailored smoking cessation programs.